Aslib Cranfield research project - A report on a test of the index of metallurgical literature of Western Reserve University - Aitchison, Jean; Cleverdon, Cyril W. (Cranfield University, 1963)
For many years the index to metallurgical literature at the Center for Documentation at Western Reserve University has been recognised as one of the most advanced indexing systems in use. It has been developed over many years with the assistance of grants from the American Society of Metals, and was put on an operational basis in 1960, when it was made available to members of the Society by subscription. At Cranfield, a by-product of the test on the efficiency of indexing systems had been the development of a method for testing existing systems. The opportunity of trying-out this method on the W.R.U. index was greatly appreciated by the Cranfield group; that it was an experiment in the use of the technique, equally as much as a test of the W.R.U. index, was accepted by both groups from the start. However, as the work developed, it became clear that the test was also becoming a research investigation in its own right, and that it was making significant additions to our knowledge of the operation of indexing systems. The following report covers all three stages of the work.